Preparation and characterization of hydroxyapatite powder and study of hydroxyapatite - alumina Composite. (July 2020) - Saeed, Ghazi K.; Essa, Abbas F.; Said, Saja Abdul-Ammer
Abstract: Hydroxyapatite powder Ca10 (PO4 )6 (OH)2 was prepared locally from Iraqi beef bones, and characterization the powder as well as studied purity. A composite of hydroxyapatite-alumina was also prepared with a ratio of alumina 0, 5, 10, 15, 20, 25% wt. Use polyethylene glycol as a binder with 1% wt by dissolving polyethylene glycol with ethanol (1g: 100ml) at 40 °C and using a magnetic stirrer to obtain a homogeneous solution for the material. Then drying the powder and pressing to prepare compound samples, after that heat treatment at 1350°C for three hours. The physical and mechanical properties studied such as density, porosity, water absorption ratio, hardness and compression resistance, as well as X-ray diffraction and X-ray florescence. X-ray diffraction analysis showed that the hydroxyapatite phase was stabilized for all prepared samples before and after heat treatment with chemical form Ca10 (PO4 )6 (OH)2, the hydroxyapatite showed a stabilization in phase before and after heat treatment without decomposition into different components.